Discussion of Communicative Language Teaching Approach - Lei, Tiantian (Scientific Journal of Technology, 2025)
As an important language teaching approach, the core concept of Communicative Language Teaching (CLT) is to enhance communicative competence through interactive learning of the target language. It emphasizes the introduction of authentic texts and encourages learners to participate in the classroom with their personal experiences, making the learning process more focused and personalized. The merits of CLT lay a solid foundation for learners’ future career development and social life. Although CLT also has some limitations, its remarkable effect in promoting communicative competence and personal development makes it one of the most important teaching approaches in language education nowadays.